Comparing the ganglion cell complex and retinal nerve fibre layer measurements by Fourier domain OCT to detect glaucoma in high myopia. Issue 8 (30th August 2010) - Kim, Na Rae; Lee, Eun Suk; Seong, Gong Je; Kang, Sung Yong; Kim, Ji Hyun; Hong, Samin; Kim, Chan Yun
Abstract : Aim: To compare the diagnostic ability to detect glaucomatous changes between peripapillary retinal nerve fibre layer (RNFL) thickness and the macular ganglion cell complex (GCC) in highly myopic patients using Fourier domain optical coherence tomography. Methods: Participants, consecutively enrolled from January 2009 to June 2009, were imaged with RTVue-100 (NHM4 and MM7 scan). The sensitivity and specificity of a colour code less than 5% (red or yellow) for glaucoma diagnosis were calculated. Area under the receiver operator characteristic (AUROC) curves were generated to assess the ability of each parameter to detect glaucomatous changes. Results: 73 normal controls and 77 glaucoma patients were included. Participants were categorised as 105 non-high myopes (spherical equivalent >−6.0 dioptres) and 45 high myopes (Spherical equivalent ≤−6.0 dioptres). The GCC thickness showed a strong correlation with RNFL thickness (correlation coefficient=0.763, p<0.001) in all participants. The sensitivity from superior GCC colour code was significantly higher than that from superior RNFL (p=0.019). The ability to detect glaucomatous changes in the highly myopic group by examining the average GCC thickness (AUROC, GCC; 0.889) was higher than when examining RNFL thickness (AUROC, RNFL; 0.825); however, there was no statistical significance (p=0.442). Conclusions: The ability to diagnose glaucoma with macular GCC thickness was comparable with that with peripapillary RNFL thickness in high-myopia patients. Macular GCC thickness measurements may be a good alternative or a complementary measurement to RNFL thickness assessment in the clinical evaluation of glaucoma in patients with high myopia.